Informationsressourcen: ein Handbuch für Bibliothekare und Informationsspezialisten - Gantert, Klaus; Lauber-Reymann, Margrit (Bibliotheks- und Informationspraxis, 2023)
This reliable volume provides information specialists with an up-to-date introduction to using information resources. Alongside the theoretical principles, it selects about 400 general and specialist information resources and describes their content, functions, and significance. It thus conveys basic knowledge about information resources that can be used directly in practice

GFPF & DIPF : Dokumentation einer Kooperation seit 1950 ; in Liebe zum Menschen, auf der Suche nach Wahrheit - Erich Hylla - Gesellschaft zur Förderung Pädagogischer Forschung; Frommelt, Bernd; Deutsches Institut für Internationale Pädagogische Forschung (Materialien zur Bildungsforschung, 2010)